Primary Education Didactic Renovation Principles - Shukurullo Koldoshevich Mardonov (Academia One Publishing, 2023)
the article discusses the principles of renewal of primary education didactics of our country and describes the individual approaches of the authors.
Keywords: education; elementary; didactics